2017
DOI: 10.1080/13548506.2017.1339896
|View full text |Cite
|
Sign up to set email alerts
|

Prototypes reflect normative perceptions: implications for the development of reasoned action theory

Abstract: The reasoned action approach is one of the most successful behavioral theories in the history of social psychology. This study outlines the theoretical principles of reasoned action and considers when it is appropriate to augment it with a new variable. To demonstrate, we use survey data collected from a 4–17 year old U.S. adolescents to test how the “prototype” variables fit into reasoned action approach. Through confirmatory factor analysis, we find that the prototype measures are normative pressure measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 81 publications
0
6
0
1
Order By: Relevance
“…In addition, residents' medical treatment behavior is the explicit form of residents' psychological activities and is closely related to residents' cognition. Residents' cognition determines whether a person will adopt certain medical treatment behavior intentions, and intention ultimately determines whether a certain medical treatment behavior is adopted by a person ( 15 ). Therefore, residents' cognition is indispensable for service acquisition and plays an important role in the relationship between service accessibility and choices of medical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, residents' medical treatment behavior is the explicit form of residents' psychological activities and is closely related to residents' cognition. Residents' cognition determines whether a person will adopt certain medical treatment behavior intentions, and intention ultimately determines whether a certain medical treatment behavior is adopted by a person ( 15 ). Therefore, residents' cognition is indispensable for service acquisition and plays an important role in the relationship between service accessibility and choices of medical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, this model leaves a large proportion of variance in PA behaviour unaccounted for: there is a discrepancy between what individuals plan and what they do (Rhodes & Bruijn, 2013). As a consequence, it has been suggested that health behavioural theories reflecting rational, reflective processes alone might be too narrow (Marteau et al, 2012) and that the reasoned action approach could be augmented (Hennessy et al, 2018). One possibility is that more impulsive modes of decision-making including implicit attitudes and motivations might also guide PA (Dimmock & Banting, 2009;Oliver & Kemps, 2018) especially among adolescents, whose decision-making is inclined to be influenced by spontaneous processes, especially in social situations (Blakemore & Mills, 2014).…”
Section: Introductionmentioning
confidence: 99%
“… Chew et al, 2010 , Gündüz and ğ. , 2017 , Hennessy et al, 2017 , Nevitt and Hancock, 2001 , Vandendriessche et al, 2021 .…”
Section: Uncited Referencesmentioning
confidence: 99%